Soil arthropods and natural enemies' abundances in broccoli crops treated with insecticides - MARIA HEVIYANTI; DADANG DADANG; DEWI SARTIAMI; R. YAYI MUNARA KUSUMAH; PURWANTININGSIH PURWANTININGSIH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Heviyanti M, Dadang, Sartiami D, Kusumah RYM, Purwantiningsih. 2025. Soil arthropods and natural enemies' abundances in broccoli crops treated with insecticides. Biodiversitas 26: 1698-1705. Indonesia is known as one of the countries with the highest biodiversity in the world, consisting of a rich variety of flora and fauna across terrestrial and marine ecosystems. However, the excessive and inappropriate use of synthetic insecticides has led to a significant decline in biodiversity, including the death of natural enemies and the disruption of soil microorganisms. An environmentally sustainable alternative for pest control is the application of botanical insecticides. Therefore, this research aimed to assess the effect of the application of 50EC botanical insecticide, a mixture of spike pepper (Piper aduncum) and Chinese perfume (Aglaia odorata) (2:1 w/w) extracts on Plutella xylostella population and the abundance of soil arthropods and natural enemies in broccoli (Brassica oleracea var. italica) crops. Observations of the P. xylostella population were carried out by direct observation on sample plants from the second to the ninth Week After Planting (WAP). The diversity and abundance of soil arthropods and natural enemies were assessed using pitfall traps. The results showed that the 50EC botanical insecticide demonstrated a level of effectiveness comparable to that of synthetic insecticides containing the active ingredient emamectin benzoate and microbial insecticide with an active ingredient of Bacillus thuringiensis in controlling P. xylostella. The number of arthropod individuals obtained was 6,441, belonging to 3 classes, 12 orders, 32 families, and 62 morphospecies. The order Entomobryomorpha was the most abundant, accounting for 37.96% of the total arthropod population. In terms of species richness, the order Hymenoptera was predominant, contributing 25.00% and being largely represented by the Formicidae family. The highest number of arthropod individuals (1748) was recorded in the treatment involving the 50EC botanical insecticide. These findings support the use of botanical insecticides as an eco-friendly pest control solution that can reduce pesticide residues and promote sustainable farming practices.